The Formation of Social Competence in Teachers trough Amaliyah Tadris of The Final Graduate Students of Kulliyatul Mu'allimaat Al-Islamiyah in Islamic Boarding School Darussalam Gontor for Girls 1st Campus - Akrim Mariyat; Farida Saifulloh (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2020)
The teacher has an important role in preparing good comunity members to be able to face future challenges. Therefore, teachers need to have social competence in order to able to interact and communicate with students effectively and efficiently, which teachers will be emulated by their student. But, sometimes the attitude of students who are not based on politeness, ignoring the existence of teachers, insulting and even harassing teachers is one of the anxieties in the world of education. Therefore required the determination of social competence in teachers through Amaliyah Tadris activities before the teaching-learning process. Kulliyatul Mu'allimaat Al-Islamiyah is an islamic educational institution oriented to the formation of personal teachers by implementing Amaliyah Tadris activity. This research is a qualitative descreptive study, which used some data collection techniques: interview, observation, documentation, and triangulation. While the data analiysis techniques used Miles and Huberman's data analysis, there are: data reduction, data display, and verification. The result of this study indicate that, 1) Amaliyah Tadris is the last educational touch for final graduate students is to complete and perfect superior character education. Before starting this activity, the Boarding school provided students with tarbiyah material review, teaching practices, guidance and advice. The teachers write a preparation book (i'dad) before teaching. The supervisors and other students supervise the process of teaching. After Amaliyah Tadris, all of supervisors and students finally conduct an evaluation of the teaching by the teacher which is divided into several groups. 2) The formation of social competence in teachers through Amaliyah Tadris of the final graduate students of Kulliyatul Mu'allimaat Al-Islamiyah is carried out before the activity take place, concurrent with the activity, and at the end of the activity. Begins with guidance and advice, supervised by supervision, and end with evaluation.